Post-transplant cyclophosphamide-induced cardiotoxicity: A comprehensive review - Azin Alizadehasl; Bita Shahrami; Reza Rahbarghazi; Azam Yalameh Aliabadi; Seyedeh Fatemeh Hosseini Jebelli; Yasamin Afsari Zonooz; Hoda Hakimian; Farzaneh Fathi; Sara Forati; Aysa Rezabakhsh (Journal of Cardiovascular and Thoracic Research)
Cyclophosphamide-induced cardiotoxicity, associated with its toxic metabolite acrolein, is a significant concern and unresolved issue, especially when cyclophosphamide is administrated in high doses. However, cardiotoxicity following low-dose cyclophosphamide has been also documented, especially in post-hematopoietic stem cell transplantation (post-HSCT) settings. Despite the involvement of multiple signaling pathways in cyclophosphamide-induced cardiomyopathy, the exact underlying mechanisms remain to be fully elucidated. This review outlines the current challenges of cyclophosphamide therapy in HSCT recipients. In addition, the promising therapeutic approaches by targeting acrolein’s anti-angiogenic effect were thoroughly discussed to better manage post-HSCT cyclophosphamide-induced cardiotoxicity.